KOMPETENSI SUMBERDAYA MANUSIA APARATUR TERHADAP EFEKTIVITAS PELAYANAN PUBLIK DI KANTOR CAMAT RATATOTOK KABUPATEN MINAHASA TENGGARA - PITOI, NOVLAN FERO; Pangkey, Masje Silija; Pombengi, Jericho DANGA (Sam Ratulangi University, 2016)
ABSTRACTThe purpose of this study was to determine the effect of human resource competence of theeffectiveness of public service district governments Ratatotok Southeast Minahasa Regency.This study uses quantitative methods. Research was carried by 30 votes apparatus (PNS)Ratatotok the District government. Instruments and data collection techniques used are questionnairesand aided by structured interview (interview quide). The analysis technique used to test the hypothesisis simple statistical regression analysis and simple correlation or correlation product moment.The results of data analysis provides conclusions: (1) Based on a simple regression analysis thatthe competency of HR personnel have functional relations / positive and significant impact on theeffectiveness of public services at the sub-district office Ratatotok Southeast Minahasa Regency. Thismeans that the higher / better human resource competence of the better / higher the level ofeffectiveness of public services. (2) Based on product moment correlation analysis that the competenceof human resource to correlate and power of determination / significant influence on the effectivenessof public services at the sub-district office Ratatotok Southeast Minahasa Regency. This means thatthe competence of human resource is the dominant factor in deciding the effectiveness of publicservices; that the absence of adequate human resource competencies it is difficult to expect theeffectiveness of public services can be realized optimally.Based on the results of this study, it can be recommended some of the following: (1) To improvethe effectiveness of public services in the sub-district office Ratatotok the competence of humanresource / staff should be improved, especially technical competence / functional. For that to theofficers / employees let be given education and training (training), especially technical training /functional right or in accordance with the needs and field assignments / positions these employees. (2)Given the districts is the spearhead of the district government, the public service in the sub-districtoffice personnel stationed let / employees who have sufficient competence. This is necessary becausethe reality shows that employees are generally placed in the sub-district office is a new employee orrecently lifted (inexperienced) and inadequate education.Keywords: human resource competence, effectiveness of public services.